S^1-bott functions on manifolds - Repovš, D.; Sharko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study S^1 -Bott functions on compact smooth manifolds. In particular, we investigate S_1-invariant Bott functions on manifolds with circle action.